2013
DOI: 10.1002/bdd.1858
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics, pharmacodynamics, safety and tolerability of darexaban, an oral direct factor Xa inhibitor, in healthy Caucasian and Japanese subjects

Abstract: It is concluded that single and multiple doses of darexaban are safe and well tolerated up to 240 mg with predictable PK and PD profiles in both Caucasians and Japanese, and that ethnicity does not affect its PK, PD or tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Because the 1,2-phenylenediamine framework has many advantages such as less chirality, high affinity for FXa (Franciskovich et al, 2005;Koshio et al, 2005), and ease to get, meanwhile, FXa inhibitors with this structure also possess predictable pharmacokinetics (Kadokura et al, 2013a), small interactions with food (Kadokura et al, 2013b) and no inter drug interactions (Kadokura et al, 2014). Yang et al (2015b) reported on the structural characteristics of Darexaban (Iwatsuki et al, 2011) with its glucuronic acid conjugate YM-222714 (Ishihara et al, 2014), Designed a series of FXa inhibitors with 3,4-diaminobenzidine backbone.…”
Section: Diaminobenzamides Derivativesmentioning
confidence: 99%
“…Because the 1,2-phenylenediamine framework has many advantages such as less chirality, high affinity for FXa (Franciskovich et al, 2005;Koshio et al, 2005), and ease to get, meanwhile, FXa inhibitors with this structure also possess predictable pharmacokinetics (Kadokura et al, 2013a), small interactions with food (Kadokura et al, 2013b) and no inter drug interactions (Kadokura et al, 2014). Yang et al (2015b) reported on the structural characteristics of Darexaban (Iwatsuki et al, 2011) with its glucuronic acid conjugate YM-222714 (Ishihara et al, 2014), Designed a series of FXa inhibitors with 3,4-diaminobenzidine backbone.…”
Section: Diaminobenzamides Derivativesmentioning
confidence: 99%
“…Food effect is a major drawback of LB30870 as a potential oral anticoagulant. A predictable dose–response relationship is one of the important requirements for new generation oral anticoagulants, which offer physicians and patients a number of alternative therapeutic agents, unlike warfarin, with no need for laboratory monitoring. , Food effect or food–drug interaction generally means BA change of a drug caused by food intake and can unintentionally reduce or increase the drug exposure, thereby resulting in therapeutic failure or increased toxicity. This may adversely affect patient care and contribute to morbidity and longer treatment time or hospitalization .…”
Section: Introductionmentioning
confidence: 99%
“…[5] As alternatives to VKAs, direct thrombin inhibitors (DTI) and direct factor Xa inhibitors ware proved to be effective at reducing arterial and venous thrombosis in patients with cardiovascular disease because it has become evident that inhibition of factor IIa (FIIa, or thrombin) and factor Xa (FXa) is expected to reduce or prevent clotting. [6] Thrombin is a serine protease, which converts fibrinogen to fibrin and activates factor V, factor VIII and factor IX. [7] FXa belongs to a family of trypsin-like serine proteases, and plays a central role in the production of thrombin and the activation cascade of the blood coagulation system, linking the extrinsic and intrinsic activation pathways.…”
Section: Introductionmentioning
confidence: 99%